The Stepping stones to success: how we achieve high ownership and reflective learning in multistakeholder processes in Uganda? - Sartas, Murat; Muchunguzi, P.; Sole, A.; Lamers, D.; Namazzi, S.; Awori, M.; Schut, Marc; Tenywa, M.M.; Leeuwis, Cees; Asten, Piet J.A. van (CGIAR Research Program on Integrated Systems for the Humid Tropics, 2015)
Utilization of systems approach using multistakeholder platforms as modality of intervention has been increasingly experimented in agricultural research in tropical zones. Recent research findings indicated strong evidence of the positive contribution of research for development (R4D) and innovation platforms (IP) in increasing the impact of research for development interventions. However, specific factors of the platforms leading to higher impact yet to discovered. This study assesses the success factors for achieving ownership and stakeholder engagement in Humidtropics R4D and IP platforms located in Mukono-Wakiso and Kiboga-Kyankwanzi